Pengaruh Customer Relationship Management (CRM) Terhadap Loyalitas Pelanggan Unipin - Ali Ibrahim; Muhammad Hidayat Mauluddin; A Wendi Saputra; Astri Carolina; Maya Mardiana; Yeremia Wiratama; Rofiqul Rahman Ramadhan (Journal of Information System Research (JOSH), 2021)
This research was conducted with the intention of seeing how big the impact of CRM and customer satisfaction on Unipin's customer loyalty. UniPin is a game voucher payment startup from Indonesia. Unipin implements CRM in its business. The method applied in this research is quantitative method, in which data collection is done by distributing questionnaires. The results of this study indicate that CRM has a significant effect on customer loyalty with a significance value of 0.000 < 0.05 and T Count 5.192 > 2.012, and customer satisfaction does not significantly affect customer loyalty with a significance value of 0.126 > 0.05 and T Count -1560 < 2.012